Cloning, expression analysis, and the photoperiodic response of CHH gene in Panulirus homarus - Zhimin Ju; Jiajun Luo; Charles Brighton Ndandala; Chongqing Wen; Zhao Yanfei; Huafang Liang (Aquaculture Reports)
Two subtypes of the Crustacean Hyperglycemic Hormone (CHH) gene and the cDNA of Panulirus homarus (PhCHHA and PhCHH-B) were been successfully cloned and characterized in this study. The length of PhCHH-A was 1186 bp with a 384 bp open reading frame that encodes a 127 amino acid. The length of PhCHH-B was 662 bp with a 394 bp open reading frame that encodes 131 amino acids. PhCHH-A and PhCHH-B possess most of the characteristics of eyestalk type-I CHH/MIH/GIH family neuropeptides. Both have a “signal peptide, CPRP, and mature peptide” structure. Their mature peptide comprised 74 amino acids and 6 cysteine residues in a conserved position. Homology and phylogenetic analysis showed that PhCHH-A and PhCHH-B were conserved in several functional domains. They showed the highest homology with CHH of Rock lobster (Jasus lalandii). Additionally, high levels of PhCHH-A transcripts were detected in both the intestine and eyestalks, where the expression of PhCHH-B was the highest in eyestalk. In female lobsters, PhCHH-A and PhCHH-B expression levelin eyestalk gradually increased with ovarian development. The photoperiod experiment results showed that ovarian development was optimal at 14 L:10D, and the expression levels of PhCHH-A and PhCHH-B in the eyestalk increased to the peak. In conclusion, these results indicate that PhCHH-A and PhCHH-B might play a critical role in the ovarian developmental cycle of P. homarus. In addition, a photoperiod of 14 L:10D had the most apparent effect on promoting the expression of PhCHH-A and PhCHH-B, and ovarian development.